Effects of Personal Growth and Emotional Intelligence on the Subjective Happiness of Undergraduates - Komal Hassan; Noorum Ilyas; Shama Sadaf; Ayesha Saeed (Journal of Management Practices, Humanities and Social Sciences, 2021)
This study investigated the effects of personal growth and emotional intelligence on the subjective happiness of under-graduates. The approach of this research was quantitative, and a cross-sectional research design was used in this study. A sample of 400 undergraduates was selected through random sampling technique from the University of Management and Technology, University of Central Punjab, Comsats University, and the University of Punjab. Three standardized instruments (including trait emotional intelligence questionnaire; personal growth initiative scale – II developed by and subjective happiness scale developed by were used to gather data. The demographic information of the students was also collected. There are strong effects of emotional intelligence and personal growth initiative on the subjective happiness of undergraduates. It was concluded that emotional intelligence and subjective happiness relatively fluctuate depending upon undergraduates' academic workload. This research itself effectively elucidates the importance of emotional intelligence, management of stress, and personal and emotional growth when it comes to determining the subjective happiness of individuals.